(untitled) (Comprehensive Journal of Science, 2026)
This paper aims to design and implement an intelligent, multi-tasking rescue robot capable of operating in hazardous and complex environments resulting from natural disasters and industrial accidents. The goal is to support search and rescue operations and reduce risks to human personnel. The proposed system is based on a mobile robotic platform equipped with a comprehensive suite of environmental and motion sensors, including gas, temperature, and humidity sensors, a flame detector, and distance sensors. This enables the robot to monitor surrounding conditions and detect potential hazards in real time. The paper also includes the integration of a live video streaming unit (ESP32-CAM). To enable the transmission of live images and video to control centers, supporting field assessment and rapid decision-making, the system utilizes wireless communication technologies such as Wi-Fi and GSM for transmitting critical data and alerts. The robot features dual control capabilities, operating in an automated mode that relies on sensor data processing, or in a manual mode controlled remotely via smartphone. The system is equipped with a simple robotic arm powered by servo motors for removing light obstacles or handling small objects, expanding its applicability in environments prone to collapse. The prototype was built using low-cost, open-source electronic components, such as the Arduino Uno. The aim was to achieve economic viability and ease of maintenance and development. Practical results demonstrated the system’s success in performing its basic tasks efficiently and stably, confirming its potential as a prototype for developing intelligent rescue systems applicable in local and resource-limited environments.